Global Collaboration: Intercultural Experiences and Learning - Cardel Gertsen, Martine; Søderberg, A.; Zølner, M.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2012)
Offers qualitative studies of collaboration processes conducted in globalising companies based in Denmark and with subsidiaries in Asia. It addresses the specific contexts of collaboration and studies how people with different cultural backgrounds work together, both face-to-face and in the virtual workplace.
Keywords: International business enterprises; Globalization; Markets; International economics; Personnel management; Public relations; International Business; Emerging Markets/Globalization.; International Economics; Human Resource Management; Corporate Communication/Public Relations